Semantic change and knowledge transmission: Some case studies in the distribution of words in ECCO. (18th January 2022) - Regan, John
Abstract: This article attempts to make good on the affordances of lexical co-association to investigate semantic change in the British eighteenth-century corpus, mindful of the theories of knowledge that have been presented in an adumbrated state above. Pulling back to enquire into the whole of the eighteenth-century printed corpus, and designing tools fit for apprehending and making sense of such a large, impersonal, non-individual view, will result in a complementary picture of how knowledge was structured and transmitted in the eighteenth century compared with individualistic or 'great man' narratives of the history of ideas. Taking the eighteenth-century corpus as a field of enquiry (even in light of its various well-known limitations and inherent biases) results of course in a virtually total loss of granularity at the level of close reading, and a consequent turn away from individual texts written by individual people. But what replaces this is the ability to reconstitute structures of semantic expression from that time that are unexaminable at the level of the sentence and the paragraph, the chapter, and the book. As will be demonstrated, we may now make visible the printed, common, and possibly 'public' or social structures of meaning. This article's field of enquiry is the vast common printed semantic storehouse, as opposed to what is laid down by single authors in clauses, sentences, and chapters.